The integrity of hypothalamic-pituitary-adrenal axis in Boran (Bos indicus) cattle infected with Trypanosoma congolense - Abebe, G. (1991)
Many of the physiological and metabolic disturbances which are apparent during trypanosomiasis could have an endocrinological actiology. Poor reproductive performance is an abvious example. However, other features of trypanosomiasis such as loss of body weight, anaemia, poor immune responses and intolerance to stress could be manifestations of imbalance of cetain humoral factors. Trypanosoma congolense infection in Boran cattle caused a decline in basal cortisol and ACTH concentration at the time of potent parasitaemia. Whereas adrenal response to exogenous ACTH challenge was not impaired by trypanosome infection, pituitary-adrenal axis response to exogenous CRF challenge was HPA axis of infected animals totally failed to respond to insulin induced-hypogycacmia. Although not discarding a hypothalamic effect, an impairment of pituitary function is further supported by the observation, by electron microscopy, of actively dividing trypanosomes in the microvasculature of the pituitary gland of infected animals. Results support the hypothesis that the integrity of HPA axis during acute bovine trypanosomiasis is defective to an early hypothalamic-pitutary damage. A similar pituitary thyroid axis defect has been observed in these animals. Any early hypothalamic-pitutary defect during the acute phase of the disease could lead to a secondary dysfunction in target endocrine glands due to the low level or absence of pituitary-tropic hormones.